The Task of Legal Protection for Indonesian Citizens from Online Gambling Exploitation in the Perspective of Law Enforcement in the Digital Era - Abdullah, Merwan; Lismiati, Iseu; Sapsudin, Asep (Journal of Law, Politic and Humanities, 2025)
The legal protection of Indonesian citizens from online gambling exploitation is a very relevant issue along with the rapid development of digital technology that provides easy access to various forms of illegal gambling. Online gambling not only has a negative impact on an individual's economy, but can also trigger wider social and psychological problems, such as dependency and significant financial losses. This research was conducted in response to the need to evaluate the extent of prevention, enforcement and protection from online gambling exploitation in a legal perspective in the digital era in Indonesia along with its obstacles and challenges. This research is carried out with a descriptive-analytical approach, which describes the data obtained from observations, interviews, documents, and field notes, then analyzed in the form of scientific work to explain the issues raised in the predetermined juduI, namely legal protection, using a qualitative approach.The results of this study provide a clear picture of how the state's efforts to protect the public and the challenges faced in law enforcement against online gambling in Indonesia, and formulate policy recommendations that can optimize legal protection for Indonesian citizens. These recommendations include improvements in regulation, increased capacity of law enforcement in cyberspace, and prevention strategies that are more adaptive to the development of information and communication technology. The government must carry out integrated law enforcement by increasing mastery of sophisticated technology and conducting international cooperation to be able to catch online gambling actors abroad.